Influence of different systems of minimum ventilation on air quality in broiler houses - Menegali,Irene (2012)
To maintain a competitive development of the Brazilian aviculture, some measures must be taken to enable the identification and reduction of risks to the health of birds, as well as for the physical environment. Therefore, the aim of this study was to evaluate the effectiveness of three different systems of minimum ventilation (positive pressure - SVMP, negative pressure - SVMN and natural ventilation - SVMNat) in the air quality during the first 21 days of life of broiler chicks, during winter. Three points were selected along the length to verify ammonia, carbon monoxide and oxygen concentrations at 3a.m., 9a.m., 3p.m. and 9p.m., by the respiration level of birds and workers. The averages of pollutant gases did not exceed the tolerance levels for the three minimum ventilation systems evaluated, which is 20 and 10ppm for the birds level and 20 and 39ppm for the workers level, for ammonia and carbon monoxide, respectively. It was evident that the minimum ventilation systems were appropriately sized for the required minimum ambient air renovation, in respect to ventilation rates applied for the SVMN and SVMP systems, and with air velocity at levels that do not stress the chicks, including for the SVMNat. The three studied systems of minimum ventilation allowed the birds to externalize their productive performance, with values close to the ones considered satisfactory for all evaluated parameters, in accordance with the Brazilian aviculture standards.